Evaluation of investment decisions in the health sector A case study at Amir Al-Momineen Specialized Hospital - Falah, Dr. Hussein Jassim; Hussein, Hussein Ali (The journal of contemporary issues in business and government, 2023)
The importance of research in studying investment decisions in the health sector highlights the importance of this sector, and as one of the main and important pillars upon which infrastructure development depends, and the importance of using investment decision evaluation methods. To extract the highest value from its use and reduce the economic and environmental costs of the health sector, therefore there is the problem of the research (Is the health sector dependent on methods for evaluating investment decisions), and the research was applied in the Amir Al- Momineen Specialist Hospital . The researcher reached the conclusion, the most important of which is that there is a close relationship between the feasibility study and investment decisions. The more the proposed investment projects are evaluated to choose the optimal project, the more the investment decision will be in the right direction, and in light of the conclusion, the researcher recommends that companies and institutions should give a study of the investment project great attention because it is considered one of the most difficult tasks .